A bioenergetics model of the entire life cycle of the three‐spined stickleback, gasterosteus aculeatus. Issue 1 (14th December 2016) - Leloutre, Charlène; Péry, Alexandre R. R.; Porcher, Jean‐Marc; Beaudouin, Rémy
Abstract: A whole life‐cycle bioenergetic model based on the dynamic energy budget (DEB) theory was proposed for the three‐spined stickleback ( Gasterosteus aculeatus ). To develop this model, experiments on growth and reproduction were performed: adult and juvenile growth, size at first reproduction and amount of eggs spawned by females were monitored under different feeding levels and temperatures. The DEB parameters were estimated, using Bayesian statistics, based on the data produced during these experiments and on other data found in the literature. The model fitted accurately the different data used for the calibration process and, in addition, predicted accurately the data sets used to assess its predictability. Our bioenergetic model of the whole life cycle of the three‐spined stickleback accounting for environmental variations could contribute in many ways to improved ecological assessment: supporting change of scale from individual to populations; developing new biomarkers of exposure and effect; analysing ecotoxicity tests with biology‐based models.